Persepsi Petani Terhadap Kinerja Penyuluh Pertanian di Desa Torongrejo Kecamatan Junrejo Kota Batu - Chindy Feliyana; Jabal Tarik Ibrahim; Gumoyo Mumpuni Ningsih (Jurnal KIRANA, 2021)
Forest management carried out by the Panti District community in The performance of agricultural extension workers is starting to be felt by farmers, but in terms of farmers' perceptions of the performance of agricultural extension workers which are considered less than optimal because in the implementation of the extension there are obstacles such as differences in schedules between agricultural extension workers and farmer groups, many group members do not participate in extension activities. this. Regarding these obstacles, it is necessary to conduct a more in-depth study of farmers' perceptions of the performance of agricultural extension workers in Torongrejo Village, Junrejo District, Batu City. This study aims to analyze farmers' perceptions and the factors that influence farmers' perceptions of the performance of agricultural extension workers in Torongrejo Village, Junrejo District, Batu City. The technique of determining respondents in this study was simple random sampling. The number of respondents as many as 50 people is calculated based on the slovin formula. Data were collected by means of observation, interviews, questionnaires, and documentation. The analytical method used is Multiple Linear Regression with the help of SPSS (Software Program for Social Science) software. ). The ordinal scale data is converted to an interval scale with MSI (Methode of Successive Interval). Before the multiple linear regression analysis was tested, the classical assumption test, normality test, heteroscedasticity test and multicollinearity test were carried out. Based on the results of the analysis of the level of perception of farmers on the performance of the instructor as an initiator of 76%, as a motivator by 78%, as an educator by 78%, as a communicator by 79% and as a facilitator by 75% so that it can be said that the role that has been carried out by agricultural extension workers is categorized as good. The performance of agricultural instructors as initiators, motivators, educators, communicators and facilitators significantly influences the level of farmers' perceptions of the performance of agricultural extension workers. Keywords : Perception, Farmer, Performance, Extension